Pengaruh Promosi Kesehatan Metode Brain Storming terhadap Pengetahuan Kader Tentang Kelas Ibu Hamil - Riona Sanjaya; Mirna Desiyanti; Rika Agustina; Beniqna Maharani Besmaya (Universitas Muhammadiyah Manado, 2026)
The cadres play an important role in the success of the implementation of maternity classes, so their knowledge about the classes needs to be improved. At Puskesmas Bunut, KIA officers have conducted counseling using the lecture method, but the pre-survey results on 10 cadres show that 80% of them have insufficient knowledge. This study aims to determine the effect of health promotion (promkes) using the brainstorming method on the knowledge of cadres about maternity classes at UPTD Puskesmas Bunut in 2025. The brainstorming method was chosen because it can stimulate creative thinking, broaden perspectives, and enhance understanding. This research uses a quantitative design with a pre-experimental type, involving 78 cadres as samples using total sampling technique. Data was collected through pre-test, intervention using the brainstorming method, and post-test. Data analysis was done using dependent T-test. The results showed an increase in cadres' knowledge from an average of 44.23 before the intervention to 70.32 after the intervention. The dependent T-test showed a significant effect (p-value = 0.000 < 0.05). It is expected that the coordinator midwife at Puskesmas Bunut will regularly improve cadres' knowledge using the brainstorming method and conduct periodic evaluations.